Planning for development: national physical development plan background paper: 'strategies: alternative spatial concepts' (National physical development plan background papers; no. NP/BP7) - Government of the Republic of Trinidad and Tobago. Ministry of Finance (Planning and development). (Town and Country Planning Division., 2011)
Attempts to explore the possibility of generating and/or deriving a strategy or strategies from a study of tried and tested spatial concepts and forms.
Keywords: Development planning - Trinidad and Tobago, Physical planning -Trinidad and Tobago, Planning - Land use, Development - Strategic planning, Urban planning / Urban development